STUDYING THE LIVER FUNCTION IN BURN RECONVALESCENTS (Archive of Conferences, 2021)
The article discusses the results of studying the violation of the functional state of the liver in patients with extensive burn injuries. The liver function in these patients remains impaired even several months after the healing of burn wounds. We study hypoproteinemia and dysproteinemia resulting from burn injury, a decrease in the antitoxic function of the liver for a long time, manifestations of cytolytic and cholestatic syndromes, a decrease in the content of total lipids, cholesterol and beta-lipoproteins.